대동맥판부전이 동반된 상행대동맥류의 외과적 치험 - 박만실 (Taehan Hyungbu Oekwa Hakhoe chi, 1993)
We retrospectively studied 34 patients who underwent operations of ascending aortic aneurysm and aortic valve replacement from August 1979 to July 1992 at the Yonsei Cardiovascular Center. Eight patients underwent supracoroanry non-composite graft replacement and separate aortic valve replacement[group I]. Twenty six patients underwent valved composite graft replacement with reimplantation of coronary arteries[group II]. Two cases in group II died within 1 month after the operation. Among the 32 survivors 28 patients have been followed up for an average of 59 months ranging from 1 months to 159 months. During the follow up periods, a pseudoaneurysm around the ascending aorta and a newly developed dissecting aneurysm in remaining aorta were noted in group II. There were 6 late deaths: 2 cases in group I and 4 cases in group II. Three cases among the 6 late deaths have stigmata of Marfan`s syndrome[1 cases in group I and 2 case in group II]. There was no statistically significant difference in actuarial survival rates between group I and group II[p > 0.05]. This study suggests that non-composite supracoronary graft interposition with separate aortic valve replacement is a safe surgical technique in patients who have normal aortic annulus and normal position of coronary ostia. However in degenerative disease such as cystic medial necrosis, composite graft replacement is recommended because this procedure eliminates entire abnormal tissue.But it seems to be important that the suture technique and strict follow-up in patients with diseased aortic wall.